Sleep in the wild: the importance of individual effects and environmental conditions on sleep behaviour in wild boar - Mortlock, Euan; Silovský, Václav; Güldenpfennig, Justine; Faltusová, Monika; Olejarz, Astrid; Börger, Luca; Ježek, Miloš; Jennings, Dómhnall J; Capellini, Isabella (Proceedings. Biological sciences, 2024)
Sleep serves vital physiological functions, yet how sleep in wild animals is influenced by environmental conditions is poorly understood. Here we use high-resolution biologgers to investigate sleep in wild animals over ecologically relevant time scales and quantify variability between individuals under changing conditions. We developed a robust classification for accelerometer data and measured multiple dimensions of sleep in the wild boar (Sus scrofa) over an annual cycle. In support of the hypothesis that environmental conditions determine thermoregulatory challenges, which regulate sleep, we show that sleep quantity, efficiency and quality are reduced on warmer days, sleep is less fragmented in longer and more humid days, while greater snow cover and rainfall promote sleep quality. Importantly, this longest and most detailed analysis of sleep in wild animals to date reveals large inter- and intra-individual variation. Specifically, short-sleepers sleep up to 46% less than long-sleepers but do not compensate for their short sleep through greater plasticity or quality, suggesting they may pay higher costs of sleep deprivation. Given the major role of sleep in health, our results suggest that global warming and the associated increase in extreme climatic events are likely to negatively impact sleep, and consequently health, in wildlife, particularly in nocturnal animals.
Keywords: životní prostředí; Environment; Female; Sleep; biologging; spánek; double-hierarchical generalized mixed-effects models; sleep ecology; roční období; Animals; ženské pohlaví; mužské pohlaví; Male; wild boar; Sus scrofa; zvířata; pace-of-life syndrome; Seasons